Glyphosate-Resistant Canada Fleabane Control in Winter Wheat with Postemergence Herbicides - Nader Soltani; C. Shropshire; Peter H. Sikkema (International Journal of Agronomy)
In recent years, there has been a rapid increase in the number of herbicide-resistant weeds, including glyphosate-resistant (GR) biotypes in Ontario, Canada. A total of six field experiments were conducted over a two-year period (2018 and 2019) to determine the control of GR Canada fleabane (Conyza canadensis (L.) Cronq.) with currently available herbicides for winter wheat in Ontario. Winter wheat was not injured with any of the herbicides evaluated. Among herbicides evaluated, pyrasulfotole/bromoxynil (preformulated), 2,4-D ester, halauxifen, fluroxypyr/halauxifen (preformulated) + MCPA, pyrasulfotole/bromoxynil/fluroxypyr (preformulated), pyrasulfotole/bromoxynil/thiencarbazone (preformulated), pyrasulfotole/bromoxynil/thiencarbazone + MCPA, and fluroxypyr/halauxifen + pyroxsulam + MCPA controlled GR Canada fleabane 94–100% at 8 weeks after application (WAA) and reduced density 95–100% and biomass 97–100%. Reduced GR Canada fleabane interference with pyrasulfotole/bromoxynil/thiencarbazone + MCPA increased winter wheat yield 27% compared to the weedy control. GR Canada fleabane interference had no adverse effect on winter wheat yield with all other treatments. Based on these results, herbicide treatments that include 2,4-D, pyrasulfotole, or halauxifen can adequately control GR Canada fleabane in winter wheat.